Perbandingan Perlindungan Hukum Terkait Data Pribadi di Indonesia dan Jerman - Anjawai, Namrysilia Buti; Amboro, F. Yudhi Priyo; Hutauruk, Rufinus Hotmaulana (Fakultas Syariah INSURI Ponorogo, 2022)
Protection of personal data is a human right that must be given legal protection. However, Indonesia does not yet have special rules governing the protection of personal data and the Personal Data Protection Supervisory Agency. As for when compared to Germany, which has special rules regarding the protection of personal data in full to the Institution that oversees the implementation of the rules for protecting Personal Data. The research method used by the author is a legal comparison method with the type of research being normative research. The author uses secondary data to analyze the results of the data, namely, primary materials, secondary materials, and tertiary materials. The analytical method used by the author is a qualitative method. Similarities and differences in personal data protection between Indonesia-Germany and the legal contributions of personal data protection that he can adopt or apply in Indonesia such as special arrangements for personal data protection, data classification, one of which is the deletion of personal data, and the establishment of a Personal Data Protection Supervisory Agency and the rules that govern it